"He Didn't Necessarily Force Himself Upon Me, But . . . ": Women's Lived Experiences of Sexual Coercion in Intimate Relationships With Men. (July 2017) - Jeffrey, Nicole K.; Barata, Paula C.
This study examined women's subjective experiences with sexual coercion (SC), particularly less forceful forms, in intimate relationships. In-depth interviews with 12 university women highlighted that physical violence need not be present for SC to be harmful, as many experienced guilt, anger, sadness, and self-blame. The severity of SC and the context of women's relationships affected their interpretations, which in turn affected the effects of SC. Many women not only held negative interpretations of their partners' SC but also minimized and justified. Thus, the interviews were also critically analyzed for the possible influence of dominant discourses and gendered power relations.